Initial experience with the fourth generation MitraClip™: Outcomes, procedural aspects, and considerations for device selection. Issue 4 (13th April 2021) - Garcia‐Sayan, Enrique; Raghunathan, Deepa; Li, Flora M.; Dhoble, Abhijeet; Sheu, Richard D.; Jelacic, Srdjan; Reisman, Mark; Smalling, Richard W.; Mackensen, G. Burkhard
Abstract: Objectives: We present our initial experience with the fourth‐generation MitraClip™ (G4) system and propose preliminary criteria for device selection. Background: The MitraClip™ G4 system recently underwent a "controlled release" for transcatheter edge‐to‐edge mitral valve repair. The four new devices include technical improvements such as controlled gripper actuation (independent leaflet capture) and continuous left atrial pressure monitoring. To date, a patient‐specific device selection algorithm, and the technology's impact on procedural times and success, have not been described. Methods: We present an initial multi‐center experience and short‐term outcomes with the new system, suggest procedural and imaging considerations, and propose initial guidance for device selection. Results: Sixty‐one procedures performed by three operators at two centers between November 2019 and May 2020 were analyzed. At 30‐day follow‐up, there were three deaths (4.9%), four neurological events (6.6%), and seven re‐hospitalizations (11.5%). Fifty‐nine patients achieved device and procedural success (96.7%), and there was one device‐related technical issue (1.6%). Compared to the same operators utilizing the third generation MitraClip™, the G4 system resulted in a significant reduction in the median number of clips used per patient (1 IQR 1–2 vs. 2 IQR 1–3, p = .023) and a trend toward shorter device times. Conclusion: Based on our initial experience, we found that the MitraClip™ G4 system is associated with high procedural success and fewer devices needed per procedure. The expanded device options may allow a more targeted approach to the myriad of pathologic presentations of mitral regurgitation. This early experience should provide a foundational opportunity for further refinement.